Assessing Workplace Violence: Methodological Considerations - Magnavita, Nicola; Larese Filon, Francesca; Giorgi, Gabriele; Meraglia, Igor; Chirico, Francesco (La Medicina del Lavoro, 2024)
The risk of violence is present in all workplaces. It must be accurately assessed to establish prevention and protection measures tailored to the features of each situation. The risk management process requires compliance in a sequential order: 1) risk identification, 2) quantitative risk assessment, and 3) impact assessment. Gathering workers' experiences using lists, focus groups, or participatory ergonomics groups is necessary to identify the phenomenon. For risk assessment, spontaneous reporting of events is often insufficient. It may be complemented with two methods: systematic recording of violent events that occurred in the past year during periodic medical examinations of workers and targeted surveys. The epidemiological analysis of data from individual interviews and surveys provides the phenomenon's prevalence, incidence, and evolution. Moreover, reporting the harm suffered by victims of violence allows constructing impact matrices to allocate resources where they are most needed.